Synchrotron Radiography for a Proton Exchange Membrane (PEM) Electrolyzer. Issue 3 (17th February 2020) - Panchenko, U.; Arlt, T.; Manke, I.; Müller, M.; Stolten, D.; Lehnert, W.
Abstract: In‐plane synchrotron radiography with a resolution of a few micrometers was applied to study transport processes within a Proton Exchange Membrane (PEM) electrolyzer cell. The degradation process of the catalyst layer, gas production with bubble formation at the catalyst layer and in the porous transport layer (PTL) was analyzed. From this, a new cell design was developed that allows for high X‐ray transmittances at the membrane plane in the in‐plane viewing direction. During the measurement, a bubble growth and movement was observed. Furthermore, a detachment of catalytic material from the catalyst layer was detected. Afterwards, a post mortem EDX analysis was conducted to determine the position of the catalyst particles. Despite Iridium being initially used as the anode catalyst and platinum as the cathode catalyst, the EDX measurement revealed Pt and Ir particles on both electrodes following cell operation.